COVID-19 Vaccine Attitudes among Allergy Patients in Babylon: A Cross-Sectional Study - Abdul Hussein Mahdi , Tamara; Saaed , Ammar; Abdul-Ameer , Marwa; Adil Ali, Ahmed; Hasan Jebur , Ahmed (Hammurabi Journal of Medical Sciences, 2024)
Background: COVID-19 vaccine hesitancy is a global health problem, particularly among individuals with allergic diseases who fear severe allergic reactions as a side effect. Objectives: This study explores attitudes towards COVID-19 vaccine acceptance and refusal among patients with various allergic disorders and identifies their primary sources of vaccine information. Materials and Methods: A cross-sectional study was conducted at a specialized center for sensitivity in Babylon, Iraq, from September 30, 2023, to June 30, 2024. The study included 1,211 patients with allergic disorders who provided verbal consent. Data were collected through personal interviews using a validated data collection form. Results: The mean age of the study group was 39.82 years (± 14.9 SD), and 57.1% were females. The most prevalent allergic diseases were allergic rhinitis (28.3%) and urticarial (27.4%). Vaccine acceptance was 62%, with significant differences based on gender, occupation, academic achievement, marital status, economic status, residence, and tobacco use (p < 0.05). Family history of allergic diseases was associated with lower acceptance (p = 0.019). The most common sources of information were family/local community (39.6%) and healthcare centers (30%), both associated with higher acceptance rates (p = 0.00). Conclusion: This study revealed a 62% COVID-19 vaccine acceptance rate among allergy patients in Babylon, Iraq. Factors associated with higher acceptance included male gender, government employment, higher education levels, and receiving information from healthcare providers. Efforts to combat misinformation and provide accurate information through trusted sources may help improve vaccine uptake in this population.